Anorectal hemangioma, a rare cause of lower gastrointestinal bleeding, treated with selective embolization: A case report - Pospisilova, Barbora; Frydrych, Jaromir; Krajina, Antonin; Örhalmi, Julius; Kajzrlikova, Ivana M; Vitek, Petr (World journal of gastrointestinal surgery, 2024)
BACKGROUND: Anorectal hemangioma is a rare and frequently misdiagnosed cause of lower gastrointestinal (GI) bleeding. Here, we present a minimally invasive therapy with selective embolization. CASE SUMMARY: A 21-year-old male patient experienced painless rectal bleeding since childhood and was treated for ulcerative colitis. Diagnostic studies later revealed specific characteristics for vascular lesions-anorectal hemangiomas. The severity of rectal bleeding caused symptomatic anemia and possible surgical treatment was associated with a high risk of fecal incontinence. Here, we present selective embolization, a minimally invasive therapeutic approach that is proven as an alternative therapeutic method of choice. The patient significantly improved temporarily and had a small ischemic ulcer, which healed with a control colonoscopy and developed no stenosis. CONCLUSION: Awareness of the clinical and radiological features of GI hemangiomas may help improve diagnostics and avoid inappropriate therapeutic procedures.
Keywords: Gastrointestinal hemorrhage; Phlebolith; Vascular malformation; Rectal bleeding; Case report; Hemangioma; Selective embolization